PENGARUH KOMUNIKASI TERHADAP KINERJA PEGAWAI PT BANK SUMUT CABANG TELUKDALAM - Amelia Risky Hulu (Universitas Nias Raya, 2023)
The problem of this research is the gap between what is determined as a policy and the reality of policy implementation. The purpose of this study is to determine the effect of communication on the performance of employees of PT Bank Sumut Telukdalam Branch. This type of research is quantitative. The type of data used is primary data and the data source is obtained through distributing questionnaires to employees of PT Bank Sumut Telukdalam Branch. The data analysis method used is simple regression. The results of this study indicate that the results of the study through the t test, where the t-test value, which is 6.672, is greater than the t-table = 1.694 and the arithmetic significance value is 0.000 alpha level 0.05. Thus it is concluded that communication has a positive and significant effect on the performance of employees of PT. Bank Sumut Telukdalam Branch. Suggestions put forward by researchers are the leadership of PT. Bank Sumut Telukdalam Branch needs to have the ability to manage communication issues within the organization to maintain good communication values ​​to employees within the organization in order to boost employee performance in carrying out tasks so that work performance is realized.